Question Number 113886 by Aina Samuel Temidayo last updated on 16/Sep/20

Answered by MJS_new last updated on 16/Sep/20

(a)

Commented byAina Samuel Temidayo last updated on 16/Sep/20

Solution please?

Commented byMJS_new last updated on 16/Sep/20

lol... just use your brain

Answered by Rasheed.Sindhi last updated on 16/Sep/20

a^x =(x+y+z)^y ,a^y =(x+y+z)^z ,a^z =(x+y+z)^x   a=(x+y+z)^(y/x) =(x+y+z)^(z/y) =(x+y+z)^(x/z)           (y/x)=(z/y)=(x/z)=((x+y+z)/(x+y+z))=1         y=x,z=y,x=z        x=y=z=k(say)  a^k =(k+k+k)^k   a=3k  k=a/3=x=y=z

Answered by Rasheed.Sindhi last updated on 17/Sep/20

Multiplying all the three  a^(x+y+z) =(x+y+z)^(x+y+z)   a=x+y+z...................A  a^x =a^y ,a^y =a^z ,a^z =a^x   (a^x /a^y )=(a^y /a^z )=(a^z /a^x )=1  a^(x−y) =a^(y−z) =a^(z−x) =a^0   x−y=y−z=z−x=0  x=y=z=k(say)  In  A  a=k+k+k=3k⇒k=a/3  k=x=y=z=a/3